Cine, política y (post)estado. La libertad de Lisandro Alonso - Laura M. Martins (Centre de Recherches sur les Mondes Américains, 2010)
This paper analyzes La libertad (Freedom) (2001) by Lisandro Alonso, perhaps one of the most radical Argentine filmmakers within the so-called New Argentine Cinema “movement.” By giving the working body a central place in the image itself, this film exposes the precarization of the labor conditions and the dissolution of the sense of community as a direct effect of the politics of neo-liberalism. But La libertad is also a meditation on cinema itself, the statute of contemporary image in late capitalism, and the possibility of a certain haptic visuality.